Active traffic management strategies for expressways based on crash risk prediction of moving vehicle groups. (December 2021) - Ma, Wanjing; He, Ziliang; Wang, Ling; Abdel-Aty, Mohamed; Yu, Chunhui
Highlights: Active traffic management strategies based on crash risk prediction are proposed. A coordinated control strategy for optimal combination of VSL and RM is established. The crash risk prediction model and control strategies take the moving vehicle groups containing connected vehicles as the analysis object. VSL-RM is superior to VSL and RM in reducing crash risk and conflict count. Abstract: Active traffic management (ATM) strategies are useful methods to reduce crash risk and improve safety on expressways. Although there are some studies on ATM strategies, few studies take the moving vehicle group as the object of analysis. Based on the crash risk prediction of moving vehicle groups in a connected vehicle (CV) environment, this study developed various ATM safety strategies, that is, variable speed limits (VSLs), ramp metering (RM), and coordinated VSL and RM (VSL-RM) strategies. VSLs were updated to minimize the crash risk of multiple moving vehicle groups in the next time interval, which is 1 min, and the updated speed limits were sent directly to the CVs in the moving vehicle group. The metering rate and RM opening time were determined using mainline occupancy, the crash risk of upcoming moving vehicle groups, and the predicted time at which moving vehicle groups arrived at the on-ramp. The VSL-RM strategy was used to simultaneously control and coordinate traffic flow on the mainline and ramps. These strategies were tested in a well-calibrated and validated micro-simulation network. The crash risk index and conflict count were utilized to evaluate the safety effects of these strategies. The results indicate that the ATM strategies improved the expressway safety benefits by 2.84–15.92%. The increase in CV penetration rate would promote the safety benefits of VSL and VSL-RM. Moreover, VSL-RM was superior to VSL and RM in reducing crash risk and conflict count.